Distinct molecular pathways mediate glial activation and engulfment of axonal debris after axotomy. - Ziegenfuss, J.S.; Doherty, J.; Freeman, M.R. (Nature Neuroscience, 2012)
Glial cells efficiently recognize and clear cellular debris after nervous system injury to maintain brain homeostasis, but pathways governing glial responses to neural injury remain poorly defined. We identify the Drosophila melanogaster guanine nucleotide exchange factor complex Crk/Mbc/dCed-12 and the small GTPase Rac1 as modulators of glial clearance of axonal debris. We found that Crk/Mbc/dCed-12 and Rac1 functioned in a non-redundant fashion with the Draper transmembrane receptor pathway: loss of either pathway fully suppressed clearance of axonal debris. Draper signaling was required early during glial responses, promoting glial activation, which included increased Draper and dCed-6 expression and extension of glial membranes to degenerating axons. In contrast, the Crk/Mbc/dCed-12 complex functioned at later phases, promoting glial phagocytosis of axonal debris. Our work identifies new components of the glial engulfment machinery and shows that glial activation, phagocytosis of axonal debris and termination of responses to injury are genetically separable events mediated by distinct signaling pathways.